Feeling through Empathy, Judging through Sympathy: Environmental Ethics and Eco-terrorism in Fiction - Chinchilla Mora, Leonardo (2024)
This research paper explores the environmental ethics depicted in Kim Stanley Robinson’s latest eco-fictional novel The Ministry for the Future (2020) through an analysis of empathy, sympathy, and environmental justice. It also seeks to challenge the common division of empathy and sympathy reactions from characters as different from those of people in real life situations to theorize a case for how people might better react and understand their role in the face of climatic crisis as a consequence of reading fiction. In so doing, it accentuates the importance of reading environmental literature to awaken readers’ sensitivities and trace paths outside the “planetary crisis” (Ghosh, 2021). Methodologically, it borrows concepts from reading-response criticism (character, empathy, and sympathy) to navigate the fabric of eco-criticism: the ethics of climate change through the injustices portrayed in Robinson’s novel. In addition to this two-dimensional approach, this paper is clearly divided in three main sections. In the first section, I approach empathy and sympathy in various ways including the former being the precursor of the later for rhetorical purposes; that is, it is unique in the making of resonances for readers. Also, I argue that readers are lured to feel empathy through the novel’s imagery and through readers’ predilection to “read minds” (Zunshine, 2006) or take “imaginative leaps” (Sutrop, 2000). The second section inspects unity through climate outrage and nation-wide agency in the aftermath of the Indian heatwave. Such unity scaffolds the last section. The third part searches an ethical dimension to eco-terrorism in the novel given a shift of national intersubjective Indian unity that entitles climate justice to their own hands. This investigation concludes by suggesting directions to an analysis of empathy and sympathy within the realm of realistic, climate fiction.